DISTRIBUTION OF FE-NI-CU SULFIDE MINERALIZATION IN THE ROCKS OF THE BURAKOVSKO-AGANOZERSKIǐ LAYERED INTRUSION - Semenov V.S.; Semenov S.V.; Zil'bershteǐn A.Kh.; Korneev S.I.; Kol'tsov A.B.; Yakovleva O.A.; Grinevich N.G. (My University, 2004)
The distribution of Fe-Ni-Cu sulfide mineral in the section of the layered complex and their characteristics were discussed. The intercalation of low- and high-sulfur sulfide assemblages in the rocks of the Aganozerskiǐ block coincided with petrographic rhythms. The formation of relatively high-grade sulfide mineralization was related to the processes of late magmatic redeposition of ore matter under conditions of extensional deformations generated at the boundaries between rocks of contrasting compositions. It was shown that the formation of sulfides in amygdaloidal segregations could be related to the postmagmatic interaction of inclusion material with the host mineral.